Forever, Jack - Boyd, Natasha (Headline Publishing Group, 2013)
When Hollywood movie star Jack Eversea stumbled into sleepy Butler Cove, he had no idea he would encounter the only 'real' thing that's ever happened to him - only to let her slip through his fingers. Small-town girl Keri Ann Butler's life changed the night she met Jack Eversea. But suddenly he was gone, and she had to pick up the pieces and start again. Now Jack is back, with one thing on his mind. Winning back the girl who stole his heart. Whatever it takes. But is it too late?